Novel Loci Controlling Parasite Load in Organs of Mice Infected With Leishmania major, Their Interactions and Sex Influence - Kobets, Tatyana; Čepičková, Marie; Volkova, Valeriya; Sohrabi, Yahya; Havelková, Helena; Svobodová, Milena; Demant, Peter; Lipoldová, Marie (Frontiers in Immunology, 2019)
Leishmaniasis is a serious health problem in many countries, and continues expanding to new geographic areas including Europe and USA. This disease, caused by parasites of Leishmania spp. and transmitted by phlebotomine sand flies, causes up to 1.3 million new cases each year and despite efforts toward its functional dissection and treatment it causes 20-50 thousands deaths annually. Dependence of susceptibility to leishmaniasis on sex and host’s genes was observed in humans and in mouse models. Several laboratories defined in mice a number of Lmr (Leishmania major response) genetic loci that control functional and pathological components of the response to and outcome of L. major infection. However, the development of its most aggressive form, visceral leishmaniasis, which is lethal if untreated, is not yet understood. Visceral leishmaniasis is caused by infection and inflammation of internal organs. Therefore we analyzed the genetics of parasite load, spread to internal organs, and ensuing visceral pathology. Using a new PCR-based method of quantification of parasites in tissues we describe a network-like set of interacting genetic loci that control parasite load in different organs. Quantification of Leishmania parasites in lymph nodes, spleen and liver of from infected F2 hybrids between BALB/c and recombinant congenic strains CcS-9 and CcS-16 allowed us to map two novel parasite load controlling Leishmania major response loci, Lmr24 and Lmr27. We also detected parasite-controlling role of the previously described loci Lmr4, Lmr11, Lmr13, Lmr14, Lmr15 and Lmr25, and describe 8 genetic interactions between them. Lmr14, Lmr15, Lmr25 and Lmr27 controlled parasite numbers in liver and lymph nodes. In addition, Leishmania burden in lymph nodes but not liver was influenced by Lmr4 and Lmr24. In spleen, parasite load was controlled by Lmr11 and Lmr13. We detected a strong effect of sex on some of these genes. We also mapped additional genes controlling splenomegaly and hepatomegaly. This resulted in a systematized insight into genetic control of spread and load of Leishmania parasites and visceral pathology in the mammalian organism.